Foundations of Human Resource Development, Third Edition, 3rd Edition - Swanson, Richard (Berrett-Koehler Publishers, 2022)
The third edition of this classic is a must-have text for the human resource development (HRD) profession. It has with brand-new material on the impact of technology, globalization, and emerging business trends on HRD practice. Human Resource Development is a large field of practice but a relatively young academic discipline. For the last two decades, Foundations of Human Resource Development has fulfilled the field's need for a complete and thoughtful foundational text. This essential text provides an up-to-date overview of the HRD profession, along with the terminology and processes required for sound HRD research and practice. Readers will gain a basic understanding of • HRD models and theories that support best practice • History and philosophical foundations of the field • HRD's role in learning, performance, and change in organizations This new edition has been updated throughout and contains new chapters on assessment, technology, globalization, and future challenges. Examples of best practices are included, along with variations in core thinking, processes, interventions, tools, and much more. This must-have reference will help both practitioners and academics add clarity to their professional journeys.
Online resource; Title from title page (viewed March 8, 2022)
Keywords: Employees -- Training of; Personnel management; Manpower planning; Human capital; Inservice Training; Personnel Management; Personnel; Formation; Personnel; Direction; Main-d'uvre; Planification; Employees; Training of